Methods for Measuring School Effectiveness - Angrist, Joshua D.,Hull, Peter,Walters, Christopher R. (National Bureau of Economic Research, 2022)
Many personal and policy decisions turn on perceptions of school effectiveness, defined here as the causal effect of attendance at a particular school or set of schools on student test scores and other outcomes. Widely-disseminated school ratings frameworks compare average student achievement across schools, but uncontrolled differences in means may owe more to selection bias than to causal effects. Such selection problems have motivated a wave of econometric innovation that uses elements of random and quasi-experimental variation to measure school effectiveness. This chapter reviews these empirical strategies, highlighting solved problems and open questions. Empirical examples are used throughout
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Schule; Bildungsertrag; Messung; IV-Schätzung; Bayes-Statistik; Bayesian Analysis: General; Instrumental Variables (IV) Estimation; General; Analysis of Education; Education and Inequality